STEM Learning Using the RADEC Model on Elementary School Students' Electrical Materials in Improving Students' Science Literacy Skills - Nanda Oktavia; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify the potential to improve the science literacy of elementary school students through the application of the RADEC learning model based on the STEM approach on electrical materials. This study uses a pre-experimental design in the form of a one-group pretest-posttest design without a control group. The subjects consisted of 21 grade V students in one of the public elementary schools in Indonesia. Data was collected through science literacy tests administered before and after learning. The results of the analysis using paired t-tests showed a significant increase in students' science literacy scores after the intervention (t(20) = 10.46, p < 0.001), with an average pretest score of 1.44 and a posttest of 4.11, as well as an average gain of 2.67 (SD = 0.80). All participants showed an increase in scores. These findings indicate that the integration of STEM approaches in the RADEC model has the potential to improve students' understanding of science concepts. However, because the study design did not involve a control group, it cannot be concluded with certainty that the improvement was entirely due to the intervention. Other factors such as additional learning experience or the effect of test repetition can affect the results. Further research with a quasi-experimental design is recommended to test effectiveness more robustly.